Modern trends in structural and solid mechanics 1 : statics and stability - Challamel, Noël; Kaplunov, J. D.; Takewaki, Izuru (ISTE, Ltd. ; Wiley, 2021)
This book - comprised of three separate volumes - presents the recent developments and research discoveries in structural and solid mechanics; it is dedicated to Professor Isaac Elishakoff. This first volume is devoted to the statics and stability of solid and structural members. Modern Trends in Structural and Solid Mechanics 1 has broad scope, covering topics such as: buckling of discrete systems (elastic chains, lattices with short and long range interactions, and discrete arches), buckling of continuous structural elements including beams, arches and plates, static investigation of composite plates, exact solutions of plate problems, elastic and inelastic buckling, dynamic buckling under impulsive loading, buckling and post-buckling investigations, buckling of conservative and non-conservative systems and buckling of micro and macro-systems.
Keywords: Structural analysis (Engineering); Statics.; elektronické knihy; electronic books